2022
DOI: 10.3390/ijerph19031669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Longitudinal and Transverse Foot Arch on the Position of the Hallux and Fifth Toe in Preschool Children in the Light of Regression Analysis

Abstract: The aim of the study was to analyze the development of foot structure and the impact of longitudinal and transverse arching of the foot on the position of the hallux and fifth toe in preschool children. The study was carried out among 200 children aged 6 (100 G, 100 B). The research tool was the podoscope CQ-ST. The collected research results were analyzed with the use of the Mann–Whitney U test, Pearson Chi-square test and regression analysis. A statistically significant influence of the heel angle on the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Background Foot; It is responsible for carrying loads, reducing ground reaction force, providing adaptation to the ground, creating a rigid lever arm for effective propulsion, minimizing energy consumption and providing proprioception sense (1). The ability of the foot to perform these tasks in a healthy way depends on the preservation of the anatomical structure of the longitudinal and transverse arches of the foot (2,3). Disruption of the structure of the arcus pedis longitudinalis medialis (APLM), located on the inside of the foot and formed by the os calcaneus, os talus, os naviculare, ossa cuneiforme and ossa metatarsi I, II, III, causes foot deformities such as pes planus and pes cavus (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Background Foot; It is responsible for carrying loads, reducing ground reaction force, providing adaptation to the ground, creating a rigid lever arm for effective propulsion, minimizing energy consumption and providing proprioception sense (1). The ability of the foot to perform these tasks in a healthy way depends on the preservation of the anatomical structure of the longitudinal and transverse arches of the foot (2,3). Disruption of the structure of the arcus pedis longitudinalis medialis (APLM), located on the inside of the foot and formed by the os calcaneus, os talus, os naviculare, ossa cuneiforme and ossa metatarsi I, II, III, causes foot deformities such as pes planus and pes cavus (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…At present, children's orthopedic surgeons' diagnosis and curative evaluation of foot deformities such as flatfoot and high-arched foot still mainly depend on the longitudinal arch of the foot, ignoring the TAA of the foot ( 17 ). Venkadsan M et al found that the TAA of the foot can affect the flexibility of the longitudinal arch of the foot through the function of the soft tissue between the metatarsal bones.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the collapse of foot TAA is prone to irregular pain and painful callose of the foot. The deformation of foot TAA is closely related to many foot diseases in children ( 17 , 18 ). Puszczalowska-Lizis, Ewa et al reported that reduction of the transverse arch of the foot has an effect on the severity of fifth toe flexion, leading to disorders of the middle phalangeal joint ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation